Evaluation of quality management practices system in palm oil supply chain: the case of upstream / Luqman Hakim Zulkifle and Nabila Huda Aziz - Zulkifle, Luqman Hakim; Aziz, Nabila Huda (Faculty of Plantation and Agrotechnology, 2018)
Some oil palm organization has yet developed a tool to access quality management practices in the upstream. Upstream in oil palm supply chain include the growing sector involved in the cultivation of oil palm that include nursery establishment, plantation of palm oil plant and production of fresh fruit bunches (FFB). Besides, oil palm industry players have raised and issued that the quality management practices are not continuously been practice and there are various current quality management practices implemented in palm oil industry today. This research attempts to identity' the current quality management practices in palm oil upstream supply chain and to develop tools for assessing the quality management practices for industry by using qualitative method. This research using Design Science Research Methodology as a framework and used grounded theory methods for the Quality' Management Practices Model. The tools consist of 2 modules and each contains 2 parts which are operation and sustainability. The evaluation to test this tools had been conducted at 2 companies and be. evaluate according to parameter that have been determine. The companies that have been evaluated score 4 and 5 stars out of 5. This research has not concluded that the Quality Management Practices Model is the solution to the problem, merely a solution. This tool is created to help the industries to evaluate their plantation in quality management practices. This model needs to be improved from time to times according to the industry